Synthesis of Diverse Azolo[c]quinazolines by Palladium(II)‐ Catalyzed Aerobic Oxidative Insertion of Isocyanides. Issue 6 (20th March 2014) - Vlaar, Tjøstil; Bensch, Lisa; Kraakman, Jasper; Vande Velde, Christophe M. L.; Maes, Bert U. W.; Orru, Romano V. A.; Ruijter, Eelco
Abstract We report the palladium(II)‐catalyzed aerobic oxidative coupling of isocyanides with various (2‐aminophenyl)azoles using air as the stoichiometric oxidant. A diverse range of medicinally valuable azolo[c]quinazolines was obtained by this new approach. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>